2013
DOI: 10.1080/14036096.2012.683293
|View full text |Cite
|
Sign up to set email alerts
|

New Localism, Old Retrenchment: The “Big Society”, Housing Policy and the Politics of Welfare Reform

Abstract: The third section of the article considers the contemporary period, in particular reforms presented to parliament in 2011 that, if enacted, will provide new avenues for powerful interest groups to influence decisions that hitherto have been mainly the preserve of local government. The conclusion provides a summary of the key policy implications and theoretical issues that arise from the analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…Indeed, rather than encouraging a greater role for civil society as envisioned by the promotion of 'big society' and localism, several commentators have observed that cuts to local government, a strong source of support for community organisations and to various third sector infrastructure bodies and specialised funding streams, are likely to significantly weaken civil society's potential contribution to the provision of public goods (Wells et al, 2011a;Alcock, 2012a;Jacobs and Manzi, 2012). While asset ownership may be one route to achieving financial sustainability and independence for community organisations, research has also identified strategic tensions as community asset owners reconcile entrepreneurial acquisition of assets and identification of new funds with their commitment to place-based community concerns and social objectives (Aiken et al, 2011: 55).…”
Section: Rationales and Contexts For The Acquisition Of Assetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, rather than encouraging a greater role for civil society as envisioned by the promotion of 'big society' and localism, several commentators have observed that cuts to local government, a strong source of support for community organisations and to various third sector infrastructure bodies and specialised funding streams, are likely to significantly weaken civil society's potential contribution to the provision of public goods (Wells et al, 2011a;Alcock, 2012a;Jacobs and Manzi, 2012). While asset ownership may be one route to achieving financial sustainability and independence for community organisations, research has also identified strategic tensions as community asset owners reconcile entrepreneurial acquisition of assets and identification of new funds with their commitment to place-based community concerns and social objectives (Aiken et al, 2011: 55).…”
Section: Rationales and Contexts For The Acquisition Of Assetsmentioning
confidence: 99%
“…In particular, there has been an increased emphasis placed on individual and communal self-help in many fields in which the state's role has been reduced or reframed, including housing, health and welfare provision. A range of policy initiatives across the UK have promoted community empowerment and control in these fields for a number of years (see, for example, Jacobs and Manzi, 2012), but a noticeable trend in recent years has been the promotion of, and expressed political support for, the ownership of assets such as land and buildings by place-based community organisations. Localist policy agendas have increased and accelerated the opportunities for communities in England, Scotland, Wales and Northern Ireland to assume ownership and control of these assets, premised on the apparent ability of community organisations to better meet and reflect local needs, create social value and strengthen local democracy and citizen participation in communal life.…”
Section: Introductionmentioning
confidence: 99%
“…However, in practice such collaborative working takes time, investment and for participants to move beyond their individual interests and identify common interests. As noted by many commentaries on the Big Society and localism, while some of the policy intentions are worthy, without investment in community development they are unlikely to deliver empowerment (Bailey and Pill, 2011, Jacobs and Manzi, 2012, Sullivan, 2012. In a period of austerity, it is exactly these types of services, within planning departments and broader local government that are being cut (Hastings et.al.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the reforms of the planning system contained in the Localism Act (2010) and neighbourhood planning, this may be particularly the case in areas of high development pressure such as the South East of England and 'there is concern and criticism that these changes might result in a drastic reduction in new homes approved and built' (Buser, 2012: 12;Allmendinger and Haughton, 2012, Inch, 2012, Jacobs and Manzi, 2012, Lowndes and Pratchett, 2012, Sullivan, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…This provides a historic context and nuance and presents community planning as the latest twist in an on-going story (Jacobs & Manzi, 2012;Pollitt, 2008).…”
mentioning
confidence: 99%